2017
DOI: 10.1159/000466696
|View full text |Cite
|
Sign up to set email alerts
|

Standing Posture at Work Does Not Increase the Risk of Varicose Veins among Health Care Providers in Taiwan

Abstract: Objective: This study compared the risk of varicose veins (VV) among physicians, nonphysician health care providers (HCP), and the general population. Subjects and Methods: The Taiwan National Health Insurance Research Database was used to identify 28,844 physicians and 26,099 nonphysician HCP and an identical number of age- and sex-matched patients from the general population. Using logistic regression analyses, VV risks between physicians and the general population, nonphysician HCP and the general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Concerning the occupational categories, compared to general population, the risk of LLVV was not increased among dentists 15 , physician and non-physician 30 .…”
Section: Studymentioning
confidence: 76%
See 1 more Smart Citation
“…Concerning the occupational categories, compared to general population, the risk of LLVV was not increased among dentists 15 , physician and non-physician 30 .…”
Section: Studymentioning
confidence: 76%
“…No clinical trials were found on this topic. (Table 1 and Supplementary Table 2) Twenty one studies have explored the link between OC and LLVV: 16 cross-sectional studies, enrolling from 53 to 4,802 participants [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] , 1 retrospective study 30 , with 54,943 physicians and non-physicians, and 4 prospective studies including two conducted in the same population [31][32][33][34] , ranging from 5,447 to more than 1,600,000 participants from hospital registries in Denmark, and with a follow-up varying from 3 to 31 years.…”
Section: For Intermittent Claudication No Articles Explored the Linkmentioning
confidence: 99%
“…An identical number of age- and sex-matched participants from the general population was identified for comparison. In order to decrease the number of potential confounders, we also identified a cohort consisting of other HCPs who may share similar working environments and socioeconomic status with the dentists for comparison [1416]. The other HCPs included all the physicians, pharmacists, medical technicians, audiologists, consultant experts, clinical experts, dietitians, social workers, and language experts identified in the database we used, which were not matched with the dentists or general population.…”
Section: Methodsmentioning
confidence: 99%
“…The 2009 Registry for Medical Personnel and the Longitudinal Health Insurance Database 2000 (LHID 2000), two sub-datasets of the National Health Insurance Research Database (NHIRD), were used in this study. The 2009 Registry for Medical Personnel contains information about the specialty, date licensed, work area, hospital level, types of employment, and encrypted identification number of physicians, nurses, pharmacists, and other healthcare providers, which can be linked to the aforementioned claims data [19][20][21][22][23][24][25][26][27][28] . The LHID 2000 contains all claims data of 1 million (4.34% of the total population) beneficiaries who were randomly selected from the…”
Section: Data Sourcesmentioning
confidence: 99%
“…In the comparison among physician subgroups, we excluded residents because they did not have a specialty board, which makes it difficult to categorize them into individual physician specialty. Age was classified as four subgroups (<35, 35-49, 50-64, and ≥65) according to previous studies in healthcare professionals 22,23) . We classified the physicians into the following 15 specialties for the analysis: ear, nose, and throat (ENT), anesthesiology, orthopedics, emergency medicine, ophthalmology, family medicine, internal medicine, psychiatry, obstetrics and gynecology (Ob/gyn), pediatrics, physical medicine and rehabilitation (PM&R), radiology, dermatology, surgery, and others.…”
Section: Plantar Fasciitis Was Defined By the International Classificmentioning
confidence: 99%